Geographic dissemination of information - Loughran, Tim (Journal of Corporate Finance, 2007)
Urban companies are located near millions more potential investors and sophisticated money managers than non-urban companies. More investors are familiar with urban companies and have access to informal information about them. The stock of urban companies is also more liquid than the stock of non-urban companies. We hypothesize that these factors lead information to be spread from urban companies to other companies. Urban stock returns lead rural/small city stock returns even controlling for size, industry, and analyst coverage. Closer examination of the lead–lag relation reveals that urgent trades, which are likely to reflect short-lived information, are much more common for urban firms. Information appears to be uncovered through informal means more easily available to people physically near a company. We discuss the corporate finance implications of our findings.